Pedagogical Strategies for digital inclusion in schools today (Research, Society and Development, 2022)
The purpose of this study was to present the pedagogical strategies for digital education in schools today. Technology is increasingly becoming a more important part of education. Both software and hardware are becoming more and more important to improve the educational process. Thanks to cell phones and tablets, teachers can now deploy a variety of technologies in the classroom, including augmented reality technology. However, mobile devices themselves act as powerful computing devices today. Teachers must also look for innovative ways to integrate technology that students are used to using, such as social media networks. These technologies, along with virtual reality, 3D printing, and cloud computing, lay the foundation for creating enhanced learning environments that are engaging and effective. Today, mobile technology can be used in many ways to enhance the classroom. At a basic level, it can be used to meet basic needs, such as doing calculations, recording classroom lectures, and taking notes. However, this barely begins to scratch the surface of what mobile technology can do. This technology can be taken away during scientific field trips and used to document natural phenomena. Similarly, field trips through history can be enhanced by taking pictures of historically significant structures. The research methodology was bibliographic through the collection of information in books and articles.